Chemokine-Driven Migration of Pro-Inflammatory CD4+ T Cells in CNS Autoimmune Disease - Heng, Aaron H. S.; Han, Caleb W.; Abbott, Caitlin; McColl, Shaun R.; Comerford, Iain (Frontiers in Immunology, 2022)
Pro-inflammatory CD4+ T helper (Th) cells drive the pathogenesis of many autoimmune conditions. Recent advances have modified views of the phenotype of pro-inflammatory Th cells in autoimmunity, extending the breadth of known Th cell subsets that operate as drivers of these responses. Heterogeneity and plasticity within Th1 and Th17 cells, and the discovery of subsets of Th cells dedicated to production of other pro-inflammatory cytokines such as GM-CSF have led to these advances. Here, we review recent progress in this area and focus specifically upon evidence for chemokine receptors that drive recruitment of these various pro-inflammatory Th cell subsets to sites of autoimmune inflammation in the CNS. We discuss expression of specific chemokine receptors by subsets of pro-inflammatory Th cells and highlight which receptors may be tractable targets of therapeutic interventions to limit pathogenic Th cell recruitment in autoimmunity.